Comparison of three different satellite data on 2D flood modeling using HEC‐RAS (5.0.7) software and investigating the improvement ability of the RAS Mapper tool - Yunus Ziya Kaya; Fatih Üneş (Journal of Flood Risk Management)
Abstract Flood modeling is essential to determine and protect vulnerable areas. However, due to complexity of flooding, it is challenging to model floods with a high level of sensitivity. While many factors affect flood models' accuracy, topography is among the most critical. With developing technologies, designing high‐accuracy topographical data is becoming more feasible, especially for small catchments. In this study, the authors focus on macro‐scale modeling using different types of satellite data across the Amik Plain; a large plain with a complex stream network. SRTM, Aster, and Alos Palsar satellite data were used to create digital terrain models (DTMs). The pre‐evaluation of the results showed that even the main streams in the Amik Plain were not visible. So, the geometry of the streams was created and added to the digital elevation models using the HEC‐RAS software RAS Mapper tool. A flood in 2012 was simulated using all three improved DTMs. As a result, it is seen that an enhanced version of the DTM created from SRTM data provides the best performance for use in macro‐scale flood modeling. The usage of the RAS Mapper tool as a GIS tool also performed well in the case of DTM improvements. The DTM improvements on the satellite data for the large plains can give a fairly reasonable output instead of using high‐cost sensitive data.